Quantifying Spatial variation in environmental and sociodemographic drivers of leptospirosis in the Dominican Republic using a geographically weighted regression model - Martin, Beatris Mario; Sartorius, Benn; Mayfield, Helen J.; Restrepo, Angela M. Cadavid; Kiani, Behzad; Paulino, Cecilia Jocelyn Then; Etienne, Marie Caroline; Skewes-Ramm, Ronald; de St Aubin, Michael; Dumas, Devan; Garnier, Salome; Duke, William; et al. (Scientific reports, 2025)
Spatial variation in drivers of leptospirosis transmission in the Dominican Republic is poorly understood. To inform targeted public health interventions, we aimed to characterise risk factors and drivers of transmission on a fine spatial scale. We analysed data from 2078 participants in two provinces, Espaillat and San Pedro de Macoris (SPM), collected from a 2021 cross-sectional survey. We used geographically weighted regression to quantify associations between leptospirosis seropositivity and spatial environmental and sociodemographic data. In Espaillat, higher odds of seropositivity were associated with exposure to freshwater (OR 6.51, ranging between 5.95 and 6.99), bare ground coverage above 1.44% (OR 3.70;3.49–3.92), river density surrounding the household at the highest quartile (OR 2.43;2.41–2.45) and average precipitation in the last five years at the highest quartile (2.57; 2.52–2.65). In SPM, rat exposure was associated with higher odds of seropositivity (OR 2.59;1.23–3.14). By identifying locally important drivers of transmission, our study provides evidence to support more tailored public health interventions to optimise the control and prevention of leptospirosis.